MENINGKATKAN PEMAHAMAN PELAKSANAAN PILKADA MELALUI PENERAPAN METODE BERMAIN PERAN (ROLE PLAYING) DAN CURAH PENDAPAT (BRAINSTORMING) - Sukirno Sukirno (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2016)
The problem in this study was not yet known to the influence of the use of role playing and brain storming methods to the understanding of elections at the six graders in the second state elementary school of Kembangbahu, Kembangbahu, Lamongan which addressed at a problem of elections. The data source of the study was all of six graders in the second state elementary school of Kembangbahu, Lamongan in the academic year of 2016/2017, amounting to 16 students. This study used classroom action research that consists of several cycles with each cycles there were planning, action, observation, and reflection. Instruments used in the form of Lesson Plan (RPP), Student Activity Sheet (LKS), and classroom assessments. Analysis of the data used to obtain the data on individuals and classical learning completeness obtained from performance appraisal. The mastery of learning individuals obtained if the value / score ³ 60 and completeness of classical study obtained if the percentage of students who pass the study individuals ³ 85%. This study was conducted in two cycles of the first cycle and the second cycle. In the first cycle, there were 13 students who experience the learning completeness individuals from 16 the number of students (81.25%) showed in this cycle had not experienced in classical completeness. In the second cycle of all students experienced in learning completeness individuals (100%) This show had experienced a cycle of classical completeness. And an increase in the average value of students in the first cycle was 71.25 to 80.63 in the second cycle. Thus, it could be concluded that there were significant influence of role playing and brainstorming methods to increase the students' ability in understanding the implementation of the elections.